Finite element analysis of impact energy on spur gear - Ismail Ali, Abdul Aziz; Daing Mohamad Nafiz, Daing Idris; Mohd Hasnun Ariff, Hassan; Mohamad Firdaus, Basrawi (EDP Sciences, 2018)
In high-speed gear drive and power transmission, system impact failure mode always occurs due to the sudden impact and shock loading during the system in running. Therefore, study on the amount of impact energy that can be absorbed by a gear is vital. Impact test equipment has been designed and modelled for the purpose to study the impact energy on gear tooth. This paper mainly focused on Finite Element Analysis (FEA) of impact energy that occurred during simulation involving the impact test equipment modelling. The simulation was conducted using Abaqus software on critical parts of the test equipment to simulate the impact event and generate impact data for analysis. The load cell in the model was assumed to be free fall at a certain height which gives impact load to the test gear. Three different type of material for the test gear were set up in this simulation. Results from the simulation show that each material possesses different impact energy characteristic. Impact energy values increased along with the height of load drop. AISI 1040 were found to be the toughest material at 3.0m drop that could withstand up to 44.87N.m of impact energy. These data will be used to validate data in physical experiments in further study.